2012
DOI: 10.1042/an20120002
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial Pentose Phosphate Pathway Rates in Response to High-Glucose Environments

Abstract: ROS (reactive oxygen species) play an essential role in the pathophysiology of diabetes, stroke and neurodegenerative disorders. Hyperglycaemia associated with diabetes enhances ROS production and causes oxidative stress in vascular endothelial cells, but adverse effects of either acute or chronic high-glucose environments on brain parenchymal cells remain unclear. The PPP (pentose phosphate pathway) and GSH participate in a major defence mechanism against ROS in brain, and we explored the role and regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 99 publications
(161 reference statements)
4
100
1
Order By: Relevance
“…Takahashi et al [128] reported that acutely and chronically induced hyperglycemia increased PPP activity and glutathione (GSH) levels in astrocytic culture, in turn decreasing ROS levels. Higher PPP activity facilitates the regeneration of GSH such that cells are able to combat the higher oxidative stress level (protective role).…”
Section: Oxidative Stress At Bbb In Dmmentioning
confidence: 99%
“…Takahashi et al [128] reported that acutely and chronically induced hyperglycemia increased PPP activity and glutathione (GSH) levels in astrocytic culture, in turn decreasing ROS levels. Higher PPP activity facilitates the regeneration of GSH such that cells are able to combat the higher oxidative stress level (protective role).…”
Section: Oxidative Stress At Bbb In Dmmentioning
confidence: 99%
“…Although the mechanisms by which exogenous glucose improved outcomes are uncertain it is possible that increased blood levels of glucose, as well as increased lactate or pyruvate resulting from peripheral glucose metabolism, ensured that sufficient concentrations of these biofuels were available to meet the increased cerebral metabolic demands after TBI. This could include use of these fuels to meet energy demands within neurons and glia, or increased consumption of glucose by astrocytes to support glycolysis or pentose-phosphate pathway demands, with shuttling of lactate from astrocytes to neurons for use as fuel (Pellerin et al, 2007; Takahashi et al, 2012). Increased shunting of glucose to the pentose-phosphate pathway has been reported after TBI in rats (Bartnik et al, 2005, 2007) and humans (Dusick et al, 2007), and a neuroprotective activation of the pentose-phosphate pathway with increased glutathione production has been reported in mixed astrocyte-neuronal cultures exposed to high glucose levels (Takahashi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This could include use of these fuels to meet energy demands within neurons and glia, or increased consumption of glucose by astrocytes to support glycolysis or pentose-phosphate pathway demands, with shuttling of lactate from astrocytes to neurons for use as fuel (Pellerin et al, 2007; Takahashi et al, 2012). Increased shunting of glucose to the pentose-phosphate pathway has been reported after TBI in rats (Bartnik et al, 2005, 2007) and humans (Dusick et al, 2007), and a neuroprotective activation of the pentose-phosphate pathway with increased glutathione production has been reported in mixed astrocyte-neuronal cultures exposed to high glucose levels (Takahashi et al, 2012). We are currently determining the effects of acute glucose treatments on pentose-phosphate pathway activation after experimental TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Together with a phosphatase, it can thus repair the protein glycation caused by the pentose phosphate pathway intermediates ribose-5-phosphate and erythrose-4-phosphate [13]. There is evidence that this pathway, i.e., glucose-6-phosphate-dehydrogenase, is upregulated in the diabetic state to regenerate the NADPH necessary for the defence against oxidative stress [14][15][16]. Therefore, the activity of FN3K-RP may be of importance.…”
Section: Introductionmentioning
confidence: 95%